Management of secondary education institutions with discretionary resources, the role of academic coordination, and educational leadership - Cordero Redondo, Joan Javier (2023)
This article analyzes the management of public high school educational centers, in the academic modality, with discretionary authority, the role of academic coordination, and educational leadership at Vicente Lachner and Occidental Hight School, Cartago Regional Education, are analyzed. Specifically, it examines how educational management is achieved and sustained through the implementation of certain educational practices utilizing the discretionary authority of academic coordination and educational leadership. The research problem is associated with educational management related to the discretionary exercise of academic coordination because, when combined, they seek to implement good educational practices, which in turn are linked to the achievement of high-quality practices as a state public service. The novelty of the research object lies in the relationship between a legal category (discretionary authority), educational leadership, and academic coordination. These elements constitute the development of educational management focused on pedagogical-didactic challenges. It is concluded that academic coordination supports and coordinates academic matters; however, this expression is as ambiguous as the daily tasks performed by the person in the position. If the educational leadership's conception of coordination is broad, the tasks performed by academic coordination in the educational center can become substitutes for the responsibilities of academic management. This would represent a cognitive error and an illegal act.